A Fault-Tolerant Cache Service for Web Search Engines - Marin-Caihuan, J (2012)
Large Web search engines are constructed as a collection of services that are deployed on dedicated clusters of distributed-memory processors. In particular, efficient user query throughput heavily relies on using result cache services devoted to maintaining the answers to most frequent queries. Load balancing and fault tolerance are critical to this service. This paper proposes the design of a result cache service based on consistent hashing and a strategy for enabling fault tolerance. Performance evaluation is performed by using actual queries from a commercial search engine. The results show that the proposed cache service outperforms baseline approaches, decreases the average query response time, increases query throughput and efficiently recovers performance after processor failures. © 2012 IEEE.